PEMANFAATAN RUANG TERBATAS DALAM MENINGKATKAN KETERAMPILAN PADA MASYARAKAT DI KELURAHAN SITINJAK - Nasution, Nurul Hidayah; Harahap, Olivia Feby Mon; Harahap, Raja MP; Parlindungan, Muhammad Thohir; Nur, Muhammad; Khairunnisyah; Nikayanti, Ria; Ritonga, Siti Meiranda Hafsari; Ardina, Lili; Siregar, Marniatun; Delima, Mas; Halawa, Sirina; Natunnah, Sofiyah; Nasution, Mutiah Dina; Jufri, Soleman; Siregar, Yuli Arisyah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
The level of housing density in a settlement is followed by limited space around the house that is utilized and empowered for the yard. The existence of homeowners will also determine the form of yard utilization as part of the action of environmental conservation, waste utilization and urban agriculture education. This community service aims to improve community skills in utilizing limited space as part of the action of environmental conservation, waste utilization and urban agriculture education in the community through joint activities carried out by the team. This activity uses a participatory model that involves community components such as lurah, community leaders, neighborhood heads, and the community. The implementation of the activity was carried out with the main target being the Sitinjak Village community. The number of participants was 15 people. The location of this community service was carried out at the Sitinjak Village Head Office, West Angkola District, South Tapanuli Regency. This type of service is health promotion by providing information and demonstration of planting green beans by utilizing plastic waste in a limited space. The methods used in this activity were mung bean planting, health promotion, discussion and question and answer. The final results seen from this training activity are that most of the community can find out the materials and tools needed in the process of planting green beans in a confined space and know exactly the steps needed in the manufacturing process. All participants of the activity stated that this community service was very useful because it could increase the knowledge and skills of the community in planting green beans in confined spaces.